On Homoclinic Solutions of a Semilinear p-Laplacian Difference Equation with Periodic Coefficients. (31st October 2010) - Cabada, Alberto; Li, Chengyue; Tersian, Stepan
Abstract : We study the existence of homoclinic solutions for semilinearp -Laplacian difference equations with periodic coefficients. The proof of the main result is based on Brezis-Nirenberg's Mountain Pass Theorem. Several examples and remarks are given.